2001
DOI: 10.1046/j.0028-646x.2001.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Sink–source transition in tobacco leaves visualized using chlorophyll fluorescence imaging

Abstract: Summary• The sink-source transition of developing Nicotiana tabacum (tobacco) leaves was studied here using chlorophyll fluorescence imaging.• In accordance with leaf development, the quantum efficiency of PSII, showed a steep gradient across the leaf with increasing values towards the tip.• The linear electron transport rate (ETR) saturated at higher CO 2 concentrations in the younger, than in the mature, part of the leaf, probably due to a lower Rubisco activity or a higher CO 2 diffusion resistance.• The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
1
35
1
2
Order By: Relevance
“…The results indicated a high degree of variation both along individual primordia (from base to tip) and between primordia, both at the P3 and P4 stages, consistent with the idea that rapid changes were occurring in the capacity for electron transport around this transition. Very fast induction rates were observed in the P3 samples, consistent with P3 leaves being developing sink tissues with high levels of reduced metabolites (Turgeon, 1989;Meng et al, 2001). Slightly slower rates of wPSII induction were observed in tip regions of P4 stage primordia, consistent with our proposal that the generation of Calvin cycle intermediates, the activation of Calvin cycle enzymes, and possibly stomatal opening require more time in this tissue at this stage of leaf development.…”
Section: Photosynthetic Function In Rice Leaves Is Established At Thementioning
confidence: 64%
See 2 more Smart Citations
“…The results indicated a high degree of variation both along individual primordia (from base to tip) and between primordia, both at the P3 and P4 stages, consistent with the idea that rapid changes were occurring in the capacity for electron transport around this transition. Very fast induction rates were observed in the P3 samples, consistent with P3 leaves being developing sink tissues with high levels of reduced metabolites (Turgeon, 1989;Meng et al, 2001). Slightly slower rates of wPSII induction were observed in tip regions of P4 stage primordia, consistent with our proposal that the generation of Calvin cycle intermediates, the activation of Calvin cycle enzymes, and possibly stomatal opening require more time in this tissue at this stage of leaf development.…”
Section: Photosynthetic Function In Rice Leaves Is Established At Thementioning
confidence: 64%
“…Other than that of Kusumi et al (2010), there are few studies reporting photosynthetic measurements on very young leaves. Meng et al (2001) showed that, in the developmental gradient present in a developing tobacco (Nicotiana tabacum) leaf (the youngest used was 3.9 cm long), even regions at the base have a measurable rate of electron transport. Peterson et al (2014) reported changes in the relative abundance of PSI and PSII along maize leaves (the third leaf of 12-d-old seedlings was used) and concluded that redox mediation of chlorophyll biosynthesis may regulate photosystem assembly and thus ensure the development of a suitable PSI/PSII excitation balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been widely applied in the past during induction of photosynthesis (Bro et al, 1996;Oxborough & Baker, 1997), with changes in carbohydrate translocation (Meng et al, 2001), in response to drought (Meyer & Genty, 1999;West et al, 2005), chilling (Hogewoning & Harbinson, 2007), ozone pollution (Guidi et al, 2007;Guidi & Degl'Innocenti, 2008;Leipner et al, 2001), wounding (Quilliam et al, 2006), high light (Zuluaga et al, 2008) and infection with fungi (Guidi et al, 2007;Meyer et al, 2001;Scharte et al, 2005;Scholes & Rolfe, 1996;Schwarbrick et al, 2006) or virus (Perez-Bueno et al, 2006). With Chl fluorescence imaging is possible to detect an analysis of stress-induced changes in fluorescence emission at very early stage of stress.…”
Section: Chl Fluorescence Imagingmentioning
confidence: 99%
“…Similar results were shown by Calatayud et al (2006) in rose plants subjected to water stress. Several authors (Bro et al, 1996;Meng et al, 2001) have observed a low φPSII along the main veins and neighbouring areas, which suggests that pigment composition and concentration, water potential and stomatal function differ in cells from different regions of the leaf, contributing to spatial differences in photochemical activity (Terashima, 1992;Chaerle et al, 2003;Rezaei Nejad et al, 2006).…”
Section: Variations Of Chlorophyll a Fluorescence Parameters Throughomentioning
confidence: 99%